The Importance of Subcontracting and Its Relationship With Lean Philosophy in Automotive Industry - Sá, Sara (2022)
The automotive industry represents one of the largest economic sectors in the world and most companies in this industry involve subcontracting in their strategy. However, subcontracting is one of the possible processes that can lead to inefficiencies for companies. Since lean arises as a response to the most varied problems of companies, the main goal of this work is to understand the importance of subcontracting in the automotive sector and to understand how lean and subcontracting are related. For this, an empirical study of papers and books related to these topics was performed, concluding that subcontracting is frequently used in the automotive sector, to obtain strategic advantages, and that it supports the foundations of the lean concept, as well as the lean can help manage subcontracting. The trade-off of the transfer of activities enables organizations to be flexible, lean and agile; they can then focus on their core activities, which generate more value, while the option to subcontract generates a significant reduction in costs by transferring non-core activities. In short, these two concepts are related to each other in the context of the automotive industry.